2019
DOI: 10.1002/tox.22707
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 exposure induces systemic inflammation and oxidative stress in an intracranial atherosclerosis rat model

Abstract: Objectives: Exposure to airborne particle (PM 2.5 ) is a risk factor for intracranial atherosclerosis (ICA). Because of the established role of systemic inflammation and oxidative stress by PM 2.5 , we determined whether these processes account for PM 2.5 -mediated ICA, and also whether omega-3 fatty acid (O3FA) dietary supplementation could attenuate them.Methods: Adult Sprague-Dawley rats were exposed to filtered air (FA) or PM 2.5 and fed either a normal chow diet (NCD) or a high-cholesterol diet (HCD), ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 59 publications
2
48
0
Order By: Relevance
“…Specifically, negative effects of Nrf2 in cardiovascular diseases were reported (Barajas et al, 2011;Harada et al, 2012). Particulate matter exposure was also associated with elevated expression of Nrf2, which was abolished by protections (Guan et al, 2019), suggesting that Nrf2 indeed plays roles in PMinduced cardiotoxicity, but this role is not necessarily purely beneficial or purely detrimental. In the current study, it has FIGURE 6 | Survival Plot and MDA contents in serum.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, negative effects of Nrf2 in cardiovascular diseases were reported (Barajas et al, 2011;Harada et al, 2012). Particulate matter exposure was also associated with elevated expression of Nrf2, which was abolished by protections (Guan et al, 2019), suggesting that Nrf2 indeed plays roles in PMinduced cardiotoxicity, but this role is not necessarily purely beneficial or purely detrimental. In the current study, it has FIGURE 6 | Survival Plot and MDA contents in serum.…”
Section: Discussionmentioning
confidence: 96%
“…At present, the widely recognized mechanism of PMinduced injury is oxidative stress. Among the key factors regulating antioxidant activities, nuclear factor E2-related factor 2 (Nrf2) is a major one, which appeared to be involved in oxidative stress as a protective factor (Guan et al, 2019). Specifically, there was research reported that PM2.5 enhanced the generation of basal ROS and the levels of lipid peroxidation in Nrf2-silenced cells, demonstrating the significance of Nrf2 in maintaining redox balance (Pardo et al,FIGURE 4 | Immunohistochemistry Results of AT1R 6-8 weeks C57/B6 mice, with or without Nrf2 knockout were exposed to either filtered air or air containing particulate matter (PM) for six weeks, and then the vascular tissues were collected,embedded in paraffin and subjected to immunohistochemistry for AT1R.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the activated Nrf2 regulates the proteins with antioxidant activities, such as superoxide dismutase (SOD), catalase (CAT), heme-oxygenase 1 (HO-1), glutathione peroxidase 1 (GPx-1) and NAD(P)H: quinone oxidoreductase 1 (Tebay et al, 2015). Recent evidences suggested that PM 2.5 could exert oxidative injuries on rat aortic endothelial cells, and the expression of Nrf2 protein in vascular endothelial cells of rats was enhanced (Feng et al, 2016;Guan et al, 2019). Nrf2 may be implicated in vascular endothelial injury induced by PM (Xing et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, PM exposure has an inflammogenic potential that triggers oxidative stress. For instance, PM 2.5 induces the activation of NADPH oxidase in lung epithelial cells [59] and in the middle cerebral artery of rats [60]. This enzyme produces superoxide anion that is a free radical and precursor of hydrogen peroxide, making a clear contribution to ROS production.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%